How ADP students navigate enablements and constraints of the programme: An exploration of structure and agency - Mogashana, D.; Case, J. M.; Williams, K. (South African Journal of Higher Education, 2022)
Academic Development Programmes (ADPs), or Extended Curriculum Programmes (ECPs), continue to play a central role in increasing access to previously marginalised students in higher education in South Africa. Using Archer’s morphogenetic approach, this study examines how a group of ADP students “made their way” through their engineering undergraduate studies. Twelve students in their fourth year of study were interviewed three times and selected university documents were analysed. The authors found that the fragmented curriculum, shortened consolidation and examination periods, and unfavourable examination timetables potentially constrained the students’ aspirations. In addition, the mainstream students and lecturers’ ideas about ADP students worsened their experience of marginalisation and exception. We also found that students experienced the mainly black student enrolment of the ADP as racial discrimination. The findings indicate that students found themselves in enormously constrained circumstances, but they also exhibited what Archer calls “corporate agency” and different “modes of reflexivity” to overcome some of these constraints. We argue that the establishment of Academic Development Programmes as separate from mainstream curricula, while enabling access to some extent, may have unintended consequences of also constraining the students for whom they are designed.